Kajian Teknis Dewatering System Tambang Pada Pertambangan Batubara - A.A Inung Arie Adnyano; Muhammad Bagaskoro (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2020)
Coal mining by PT. Tambang Bukit Tambi uses an open pit mining system where one of the factors that can affect mining is water that entering the mining area, so water control must be carried out, one of the ways is by using mine dewatering system. The purpose of this study is 1) To know the debit of water entering the mining area. 2) To design a pumping plan 3) To create an ideal sump design for handling water that entering the mining area. Based on the research, the daily discharge is 32,243.36 m3 / day where the water discharge that can be released by 2 Kenflo XA 125 / 40B pumps is 640 m3 / hour in 50.38 hours and the water control effort is made a sump that must accommodate water amounting to 19,427.26 m3 and after the calculation is obtained a trapezoid-shaped sump design with size length and surface width of 63.7 m, length and width of the base of the sum of 60.9 m and depth of 5 meters.